Angular dependence of magnetization in axially stressed FeBO₃ single crystals - Strugatsky, M.B.; Yagupov, S.V.; Naukhatsky, I.A.; Nepevnaya, N.S. (Functional Materials, 2006)
Magnetization processes in easy-plane weak ferromagnetic FeBO3 under magnetic field H and axial pressure P applied simultaneously in basal plane of the crystal have been investigated. The absence of expected orientational phase transition on the experimental curve MH(P) has been interpreted as degeneration of two magnetic phases into one in case of no parallelism between magnetic field and the pressure. Experimental curves MH(H) at fixed pressure for different values of angle between magnetic field and pressure directions have been constructed. Correlation between the theory and the experiment one can observe in this case as well.